2010
DOI: 10.1002/meet.14504701351
|View full text |Cite
|
Sign up to set email alerts
|

Building a virtual archives and preservation curriculum laboratory at Simmons GSLIS

Abstract: INTRODUCTIONThis demonstration showcases the Simmons GSLIS Digital Curriculum Laboratory (DCL), a collaborative teaching and learning environment to support the archives, preservation and cultural heritage informatics curricula. The Digital Curriculum Laboratory is a virtual space comprised of digital content, scenarios describing archival and preservation processes, metadata standards, and a set of digital asset management applications, where students problem-solve, experiment, evaluate and gain hands-on expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
6
1
Order By: Relevance
“…Citing multiple examples of work projects they feel unprepared to undertake, these responses indicate a clarion call for more hands‐on, practical work with technology, rather than theoretical discussions or brief demonstrations of software. This finding challenges the previous digital curation literature in which faculty claim students are doing an appropriate amount of hands‐on or practical work (Bastian et al, 2010; Harvey & Bastian, 2012; Kelly et al, 2013; Kim et al, 2011; Mayernik et al, 2015; Moen et al, 2012; Pratt‐SILS et al, 2013; Yakel et al, 2009, 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…Citing multiple examples of work projects they feel unprepared to undertake, these responses indicate a clarion call for more hands‐on, practical work with technology, rather than theoretical discussions or brief demonstrations of software. This finding challenges the previous digital curation literature in which faculty claim students are doing an appropriate amount of hands‐on or practical work (Bastian et al, 2010; Harvey & Bastian, 2012; Kelly et al, 2013; Kim et al, 2011; Mayernik et al, 2015; Moen et al, 2012; Pratt‐SILS et al, 2013; Yakel et al, 2009, 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…Digital curation even seemed a potential locus for archival education (Cox 2012 ). Sundry graduate education initiatives, though often funded short-term and by soft-money, attested to this optimism (Anderson et al 2011 ; Bastian et al 2010 , 2011 ; Botticelli et al 2011 ; Fulton et al 2011 ; Galloway 2011 ; Gregory and Guss 2011 ; Harvey and Bastian 2012 ; Kelly et al 2013 ; Kim et al 2011 ; Lee 2009 ; Lyon and Brenner 2015 ; Mayernik et al 2015 ; Moen et al 2012 ; Palmer et al 2008 ; Renear et al 2009 ; Yakel et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research projects for education models have been conducted with practitioner partners. 38 Bastian et al suggested that collaboration can be used particularly effectively for archival arrangement and description practices, especially for digital content and electronic records management. They envisage that practitioner partners will provide expertise in digital practices in support of a well-developed and tested syllabus.…”
Section: Connecting Theory To Practicementioning
confidence: 99%
“…They envisage that practitioner partners will provide expertise in digital practices in support of a well-developed and tested syllabus. 39 In addition to well-structured internships, individual advisement and nurturing by both instructors and practitioners are also important in the process of collaboration. Among many factors that contribute to a successful internship, Bastian found that students consider the repository supervisor the most influential.…”
Section: Connecting Theory To Practicementioning
confidence: 99%